El pensamiento social de Carlos Alberto Sacheri y la trilogía Deus Caritas Est/Spe Salvi/Caritas in Veritatede Benedicto XVI - Masserdotti, Germán (Sapientia, 2023)
The comparison between the social magisterium of Benedict XVI in Deus Caritas est/Spe salvi/Caritas in veritatetrilogy and the social thought of Carlos Alberto Sacheri focuses on three main points: the ecclesial exercise of the commandment of love of neighbour, the renewing and non-socio-revolutionary nature of Christianity in social life and the Church’s Social Teaching as caritas in veritate in re sociali. The coincidence in social matters between Benedict XVI and Carlos Alberto Sacheri is explained by the common reference to Sacred Scripture and the Tradition of the Church, the harmony between faith and reason and the unity of Faith. These coincidences are an effective prevention against distortions of the Social Doctrine of the Church, particularly in its revolutionary version.